Visual Representa of a Woman in the Semiotic Landscape of the Baltic States - Pošeiko, Solvita (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Linguistic landscape (LL) research of nine cities of the Baltic States shows that feminine discourse is of an essential significance in the public space. This is linguistically proved by feminine person’s names in ergonyms, also by female ergonyms and graffiti themes. However, there are multi-modal advertisements reflecting women and female items in the public space, and they are to be viewed from the perspective of the semiotic landscape. There are 294 photos reflecting a woman excerpted from the LL data base to describe visual images of a woman, focusing on the archetypes and concepts on woman’s role in society. There is a semiotic landscape research method, perception of a visual identity in advertising marketing and pop-culture, theories of the archetypes used in research. There are theoretical issues of research discussed, as well as stated target audience described linguistically and visually in the article. Furthermore, there is a general description of the excerpted material provided emphasizing typical features and interpreting several advertisements. There is an elaborated analysis of the social roles and archetypical images of visually demonstrated women given. At the end there are conclusions and a summary.